Coping With Threats and Harassment in Politics. (2nd September 2020) - Marijnissen, Diana; Kolthoff, Emile; Huberts, Leo
Abstract : Research into the harassment of politicians and other public officials in Northern America and Western Europe demonstrates that 30–93% of politicians report having experienced harassing or stalking behaviour which can comprise serious risks for the integrity of democracy and government. This leads to intriguing questions such as: what types of threats do politicians face and how do they respond to those threats? This article presents the results of research on those questions in The Netherlands. Semi-structured interviews and Q- methodology were applied to gain insight into the different types of threats and the ways in which aldermen cope with these threats and harassments. The types of threats and harassments are diverse from verbal abuse to physical violence. Q-methodology shows three types of rather different strategies towards threats and harassment. The first attitude is combative and decisive. The second attitude is vulnerable and cautious. The third attitude is down to earth and accepting. These findings are relevant because threats and harassment, unfortunately, are becoming an inevitable part of political life nowadays. More insight into the strategies used by politicians are relevant for fighting threats and harassment towards politicians and to strengthen the resilience of politicians.